2011
DOI: 10.1371/journal.pone.0016833
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clinically Relevant Protein Targets in Prostate Cancer with 2D-DIGE Coupled Mass Spectrometry and Systems Biology Network Platform

Abstract: Prostate cancer (PCa) is the most common type of cancer found in men and among the leading causes of cancer death in the western world. In the present study, we compared the individual protein expression patterns from histologically characterized PCa and the surrounding benign tissue obtained by manual micro dissection using highly sensitive two-dimensional differential gel electrophoresis (2D-DIGE) coupled with mass spectrometry. Proteomic data revealed 118 protein spots to be differentially expressed in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 45 publications
4
55
2
1
Order By: Relevance
“…Our proteomic analysis of prostate tissue samples highlighted significant downregulation of UCHL1 in cancer compared to the surrounding benign tissue [3]. In the current study, we analyzed whether downregulation of UCHL1 in PCa is due to promoter hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Our proteomic analysis of prostate tissue samples highlighted significant downregulation of UCHL1 in cancer compared to the surrounding benign tissue [3]. In the current study, we analyzed whether downregulation of UCHL1 in PCa is due to promoter hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this manuscript is to describe an optimized protocol for the identification of molecules involved in the pathogenesis of CLL, even if this approach can be extended to other diseases and/or other sample types [16][17][18] . By comparing the proteomic profiles of 2 subsets of CLL patients, good vs bad prognosis 19 , we demonstrated that they differ in the phosphorylation status of HS1 and that its activation affects the migration and adhesion capacity of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…2D-DIGE c протеомным MS-анализом образ-цов ткани РПЖ в сравнении с нормальной тканью тех же самых пациентов показал, что дифференциаль-но экспрессируемые белки (ДЭБ) в этих 2 группах тканей вовлечены в развитие опухолевого процесса и принадлежат, по данным Gene Ontology, группам семейства HSP, сигнальных транс дукторов, метабо-лических ферментов, опухолеассоциированных про-теинов и протеинов, контролирующих цитоскелетную перестройку и окислительный стресс. Системный подход к биологическим процессам доказал также, что все эти белки связаны в сети с центральными дви-жущими элементами -c-MYC, p53, РА и ПСА, кото-рые, как известно, являются ключевыми регулятора-ми при возникновении и прогрессии РПЖ и потенциальными мишенями для терапии [12].…”
Section: том 2 обзорные статьи 19unclassified